Power Transfer Capability Recognition in Deregulated System under Line Outage Condition Using Power World Simulator - Kerur, Prakash; Chakrasali, R. L. (Journal of Electrical Engineering and Automation, 2022)
The major challenges in deregulated system are determination of available transfer capability on the interconnected transmission lines. Electricity industry deregulation is the required for creating a competitive market throughout the world, which instigate new technical issues to market participants and Power System Operators (PSO). Power transfer capability is a crucial parameter to decide the power flow in the lines for further transactions and the estimation of Transfer Capability decides the power transactions based on the safety and ability of the system. This parameter will decide if an interconnected network could be reliable for the transfer of bulk power between two different areas of the network without causing risk to system consistency. The Power Transfer Distribution Factor (PTDF) is the sensitivity index, which decides the transfer capability in the interconnected network under deregulated power systems. This experiment is conducted on IEEE-6 bus system using Power World Simulator to determine the transfer capability in deregulated system under line outage condition.
Keywords: Deregulated system; PTDF; Transfer Capacity; Transfer Limit; Power World Simulator